Large-format bipolar and parallel solid-state lithium-metal cell stacks: a thermally coupled model-based comparative study - Pang,M-C; Wei,Y; Wang,H; Marinescu,M; Yan,Y; Offer,GJ (Journal of The Electrochemical Society, 2021)
Despite the potential of solid electrolytes in replacing liquid electrolytes, solid-state lithium-metal batteries have not been commercialised for large-scale applications due to manufacturing constraints. In this study, we demonstrate that the desired energy and power output for large-format solid-state lithium-metal batteries can be achieved by scaling and stacking unit cells. Two stack configurations, a bipolar and a parallel stack are modelled and compared. With 63 cells stacked in series, we show that a bipolar stack could reach a stack voltage up to 265 V. In contrast, a parallel stack with 32 double-coated cells could achieve a nominal capacity of 4 Ah. We also demonstrate that the choice of current collectors is critical in determining the gravimetric power and energy density of both stacks. By coupling the electrochemical stack model thermally, we show that the Joule heating effects are negligible for bipolar stacks but become dominant for parallel stacks. Bipolar stacks are better due to their higher power and energy densities and lower heat generation, but a lower Coulombic stack capacity limits their performance. In contrast, parallel stacks generate more heat and require more advanced thermal management. These thermally-coupled stack models can be used as prototypes to aid the future development of large-format solid-state batteries.